Pengaruh Kinerja Keuangan dan Makroekonomi terhadap Harga Saham Sub Sektor Rokok yang Terdaftar di BEI pada Masa Pandemi Covid-19 - Riyan Riskika Pratama; Novi Permata Indah (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
The cigarette industry sector is one of the industrial sectors that is considered quite affected by the losses during the COVID-19 pandemic due to the nature of the Covid-19 virus that attacks the respiratory tract area. On December 10, 2020, all share prices of cigarette issuers moved down after the government announced a 12.5% ​​increase in excise duty for 2021. The increase in cigarette excise also affected stock prices where the majority of share prices of the four cigarette issuers decreased. This study aims to determine, test and analyze the effect of ROA, ROE, and Inflation on Stock Prices in Cigarette Sub-Sector Companies listed on the IDX during the Covid-19 pandemic. The research method used is descriptive verification, the population is Cigarette Sub-Sector Companies listed on the IDX. The sampling technique used is the saturated sample technique. The analysis tool uses multiple linear regression. The results of the study explain that partially ROA and Inflation have an effect on stock prices, while ROE has no effect on stock prices. ROA, ROE, and Inflation have a simultaneous effect on stock prices. The regression model obtained by Adjusted R Square is 40.2% with the remaining 59.8% influenced by other variables not examined. Keywords: return on asset;return on equity;inflation;stock prices.